Reliabilitas Kitab Suci dari Penemuan Gulungan Laut Mati - Agnes Ranubaya, Fransesco; Tri Wardoyo, Gregorius (Borneo Review, 2022)
The Dead Sea Scrolls are the oldest manuscripts found among the manuscripts that have served as evidence of the authenticity of the Scriptures used by Christians to this day. Therefore, study about the Scriptures becomes very interesting with the comparative evidence of the Dead Sea Scrolls. Although there are still those who doubt the authenticity of the Christian Scriptures, historical, philological, archaeological, and critical analysis from Bible scholars have proven that the Scriptures used today can be accounted for authenticity. The method used in this article is a qualitative method with descriptive analysis and verification as exposure and evidence from available sources. From the results of the discussion, it was found that the Dead Sea Scrolls along with the oldest manuscripts owned by the church such as Ben Ezra or Geniza, Hallap or Allepo Syria, and Codex Leninghard are irrefutable evidence that in terms of content, the Holy Scriptures from thousands of years ago until today have valid reliability. In other words, the discovery of the Dead Sea Scrolls is complementary and interrelated evidence that the Scriptures that have been used by Christians cannot be doubted. However, it does not rule out of possibility for people who still doubt the authenticity of the Bible by studying it through the discovery of the Dead Sea Scrolls manuscript. These findings can be used as a comparative study in studying the Old Testament Scriptures and even the entire contents of the Christian Scriptures, especially the Catholic Canon. Therefore, it is our great hope that through this writing, we can increase knowledge about the essence of the Old Testament Scriptures, the process of finding the Dead Sea Scrolls, the process of canonization to become the Scriptures used by Catholics in general.